Karakterisasi sifat fungsional pati sagu (Metroxylon sagu Rottb) dengan modifikasi taut silang sebagai bahan cangkang kapsul [Characterization of sago starch (Metroxylon sagu Rottb) functional properties with cross linking modification ascapsule shell] - Desi Mustika Amaliyah, M.T.; Hamlan Ihsan (Jurnal Riset Industri Hasil Hutan, 2021)
This study aims to determine the functional properties of natural and modified sago starch as a substitute for raw material for capsule shells from animal gelatin. Rumbia starch (Metroxylon sagu Rottb) or sago starch has good biodegradability, edibility, biocompatibility, attractive appearance, and able to withstand oxygen and physical disturbances. In this study, the optimization of the functional properties of gelatin was carried out, including viscosity, gel fraction, water vapor transmission, and swelling degree test. The stages of this research were modification of sago starch, film printing and viscosity testing, gel fraction, water vapor transmission, and swelling degree test. The results showed that the gel fraction content was 51.8% (sago starch (PS) + Poly Vinyl Alcohol (PVA)) -81.6% (modified sago starch (PSM) + kaolin), the swelling degree was 1.41% (PS). +kaolin) –2.32% (PSM+kaolin), viscosity of 2 cp (PS+PVA/kaolin) –3220 cp (PSM+kaolin)), and water vapor transmission of 58.33 g/m2h –566.25 g/m2h. The best result from cross linking was the application of modified sago starch (PSM) plus kaolin which gave the highest value for the gel fraction, degree of swelling and viscosity parameters.